Transformation of Productive Zakat for the Empowerment of Urban Poor Families - Zainal Arifin; Adamu Abubakar Muhammad; Rozi; Moch. Hoerul Gunawan; Ayu Safitri (Jurnal Pelita Raya, 2025)
Zakat, which should be a strategic instrument of social justice, is often still positioned as short-term charitable assistance rather than transformative socio-economic capital. This study proposes an understanding of productive zakat not only as an Islamic economic instrument but also as a welfare policy practice with broad implications for the configuration of social justice in Indonesian urban spaces. This study uses a non-empirical qualitative method, with a critical literature review and an integrative conceptual analysis. The results indicate that productive zakat in Indonesia will be truly meaningful only if it does not stop at mere religious jargon or a financial redistribution mechanism, but becomes a social movement that upholds structural justice in a capitalist, unequal urban ecosystem. Zakat must transcend its role as an aid and function as an agent of change that challenges the roots of poverty, reorganises the power relations between muzakki, amil, and mustahik, and restores the spirit of maqāṣid al-syarī‘ah as an ethical energy for the liberation of humans from dependence and injustice. The success of productive zakat, therefore, is not measured by the number of program success reports or nominal increases in funds, but by the courage of zakat institutions to position themselves as a space for moral resistance against an economic system that breeds inequality by proving that Islamic spirituality not only teaches compassion, but also solidarity with those who are most marginalised in the city.